2001
DOI: 10.1097/00005768-200112000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation combined with resistance training in older men

Abstract: Creatine supplementation, when combined with resistance training, increases lean tissue mass and improves leg strength, endurance, and average power in men of mean age 70 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 31 publications
7
142
0
16
Order By: Relevance
“…As with Becque et al (2000) and Bemben et al (2001), significant increases were reported in body mass and lean tissue mass in Cr supplemented subjects compared to placebo (Chrusch et al 2001 Harris et al (1992) and subjects performed a set of 5 maximal 30 seconds isometric bench press repetitions. Peak force per repetition and overall force per repetition was greater in the Cr group with respect to placebo.…”
Section: Cr Supplementation and High Intensity (Anaerobic) Exercise Pmentioning
confidence: 83%
See 2 more Smart Citations
“…As with Becque et al (2000) and Bemben et al (2001), significant increases were reported in body mass and lean tissue mass in Cr supplemented subjects compared to placebo (Chrusch et al 2001 Harris et al (1992) and subjects performed a set of 5 maximal 30 seconds isometric bench press repetitions. Peak force per repetition and overall force per repetition was greater in the Cr group with respect to placebo.…”
Section: Cr Supplementation and High Intensity (Anaerobic) Exercise Pmentioning
confidence: 83%
“…Cr has also been shown to improve lower body strength in older men but had no effect on upper body strength (Chrusch et al 2001). As with Becque et al (2000) and Bemben et al (2001), significant increases were reported in body mass and lean tissue mass in Cr supplemented subjects compared to placebo (Chrusch et al 2001 Harris et al (1992) and subjects performed a set of 5 maximal 30 seconds isometric bench press repetitions.…”
Section: Cr Supplementation and High Intensity (Anaerobic) Exercise Pmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have found no added benefit of creatine supplementation to resistance exercise training and other studies have found a small increase in lean tissue mass with no residual benefit once resistance training was stopped. [125][126][127] Creatine is a natural ingredient of food and the main source is from meat products with an average daily intake of 1 g/day. However, creatine supplementation may increase the risk of interstitial nephritis highlighting the need for particular caution about its use in older people.…”
Section: Creatinementioning
confidence: 99%
“…Uzun süreli çal›flmalarda (31), sa¤l›kl› yafll› kiflilerde kas fonksiyonlar›nda düzelmeye neden oldu¤u gösterilmifl ve k›r›lgan kifliler için potansiyel yararl› olabilece¤i düflünülmüfltür. Dozlar aç›s›ndan farkl›l›klar (0,3 mg/kg, 5 gr/gün, 20 gr/gün) görülmek-tedir (32). Ancak literatürdeki tüm çal›flmalar yararl› oldu¤unu desteklememektedir (33).…”
unclassified